Value chain hygiene practices and microbial contamination of street and market vended ready-to-eat grasshopper, Ruspolia differens in Uganda: Implications for food safety and public health - Rutaro, Karlmax; Hawumba, Joseph; Nakimuli, Jane; Mulindwa, Julius; Malinga, Geoffrey M; Baingana, Rhona (Elsevier Ltd, 2024)
Food safety is a major public health issue particularly in developing countries. Ready-to-eat street-vended foods contribute significantly to dietary intake in urban and peri-urban areas, but with elevated public health risk. In this study, hygiene and food safety practices as well as the microbial contamination in Uganda's edible grasshopper value chain were evaluated.''A total of 29 grasshopper-processing households participated, and grasshopper samples collected. Indicator pathogens were analyzed using standard microbiological methods. In Kampala 50% and in Masaka 12% households had earth floors. All households in Kampala were one or two-roomed dwellings with no separate room as a kitchen, and shared a toilet. In contrast, 59% of households in Masaka had three or more rooms, 35% had a separate room for a kitchen and 47% did not share a toilet. 83% households in Kampala and 56% in Masaka obtained drinking water from public taps. Handwashing was inadequate and none of the actors was observed to wash their hands after taking a break or handling waste. For vendors, wearing protective clothing was not common, with only 28.5% in Kampala and 30.8% in Masaka wearing an apron. Containers for vending grasshoppers were largely uncovered and the utensils for measuring the grasshoppers were left mainly uncovered. Indicator organisms, Escherichia coli and Salmonella typhimurium, were detected. E. coli was the most common contaminant, but with lower levels in Masaka compared to Kampala. S. typhimurium was mainly a burden in Kampala. Our findings demonstrate that there are enormous contributors to poor hygiene and sanitation along the edible grasshopper value chain. The existence of pathogenic bacteria such as E. coli in ready-to-eat foods imply that their consumption poses a health risk.
Keywords: Street foods Edible grasshopper Edible bush cricket Sanitation